Caretaker-reported quality of life, functionality, and complications associated with assistive mobility cart use in companion animals - Narum, Melissa; Miscioscia, Erin; Repac, Jennifer (Frontiers in Veterinary Science, 2024)
ObjectiveTo evaluate the impact of assistive mobility carts on companion animals and caretakers’ quality of life by investigating factors pertaining to caretaker satisfaction, the ability to perform daily tasks, and complication rates.Materials and methodsA 23-question survey was distributed to caretakers of animals using carts to evaluate the animal and caretakers’ quality of life, acceptance, ability to complete functional tasks, and complications. Data from canine, feline, and rabbit responses were analyzed separately.ResultsDogs and cats had improved quality of life in 62 and 57% of responses and 61 and 60% for their caretakers, respectively. There was no improvement in the quality of life of rabbits or their caretakers. Regarding the complication rate, 64% were reported to have at least one complication associated with cart use, 53% of which were wounds. Across all species, there was a reported improvement in ability to perform daily tasks and activities.Conclusions and clinical relevanceCaretakers reported that assistive mobility carts improve both companion animals’ and caretakers’ quality of life, despite high prevalence of complications, including wounds. Future studies exploring specific disease conditions and long-term outcomes will be useful for guiding clinical recommendations.